1991
DOI: 10.1083/jcb.114.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of discrete functional domains in the pro region of pre-pro-transforming growth factor beta 1.

Abstract: Abstract. A series of site-specific insertion and deletion mutants was prepared in the pro domain of transforming growth factor ,Q1 (TGFa1) encoded by simian TGF01 cDNA. These mutants were transiently ex pressed in COS-1 cells and the ability of each to be properly processed, folded correctly, and secreted was determined by immunoblot analysis of cells and culture supernatants . Insertions in regions corresponding to amino acid residues 50, 154, and 170 blocked secretion ; culture supernatants from COS-1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…ings (4,6,14) that demonstrated that the N terminus of LAP interacted with the TGF-␤1 dimer to mediate growth factor assembly, secretion, and latency.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ings (4,6,14) that demonstrated that the N terminus of LAP interacted with the TGF-␤1 dimer to mediate growth factor assembly, secretion, and latency.…”
mentioning
confidence: 99%
“…Two precursors are then covalently linked at sites within both the mature growth factor and LAP to form the small latent complex (SLC) (7-10). The SLC can be cleaved by proprotein convertases (11, 12), but LAP remains non-covalently associated with the mature TGF-␤1 dimer (13,14). During the secretory process, LAP also interacts covalently with latent TGF-␤-binding proteins (LTBPs) to form the large latent complex (LLC), and it is in this form that TGF-␤1 is secreted from the cell (7, 15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clear that LAP is implicated at different levels in TGF␤ biological activity. Previous studies have indicated that LAP plays important roles in secretion and proper folding of the mature growth factor molecule (5,11,12). Furthermore, specific binding of LAP to TGF␤ may be an important mechanism in regulating the biological functions of secreted TGF␤ (6,13).…”
mentioning
confidence: 99%
“…Sha et al (17) used deletion and insertion mutagenesis to identify regions of the propeptide important for secretion of biologically active mature TGF-␤1 and determined that amino acids between residues 50 and 80 interact with the mature peptide in the latent complex form of TGF-␤1. Elimination of all glycosylation sites on the TGF-␤1 and -␤2 propeptide prevents secretion of any mature protein (18,19), and mutation of the TGF-␤1 propeptide cysteine residues results in the secretion of differently assembled and processed forms (20).…”
Section: Macrophage Inhibitory Cytokine-1 (Mic-1)mentioning
confidence: 99%